What kinds of speeches motivate climate action? - Lukas Reinhardt; Harvey Whitehouse (Royal Society Open Science)
The scientific evidence on the harmful consequences of climate change is clear yet appeals to scientific evidence alone may not be enough to inspire sufficient climate action. We analysed the effectiveness of four different speeches in video format delivered by a Global South politician to strengthen psychological bonding with humanity at large and motivate climate action in the form of donations with samples from the US, UK and South Africa. Each speech focused on one core argument: scientific evidence, morality, globally shared life experiences or humanity’s shared ancestry. All speeches significantly increased bonding with humanity and donations. On average, the speeches were equally effective at increasing donations. The speech that appealed to humanity’s shared ancestry had a stronger effect on bonding with humanity than the other three speeches and the speeches that appealed to globally shared life experiences and humanity’s shared ancestry made participants feel less sad, angry and helpless than the speeches that appealed to scientific evidence and morality. We also present evidence on the effects of the speeches delivered by a Western academic in the UK and we discuss implications of our findings for future research and practical efforts to motivate climate action.